The Internal Microenvironment of the Symbiotic Jellyfish Cassiopea sp. From the Red Sea - Silvia Arossa; Alan Barozzi; Matteo Callegari; Shannon G. Klein; Anieka J. Parry; Shiou-Han Hung; Alexandra Steckbauer; Manuel Aranda; Daniele Daffonchio; Carlos M. Duarte (Frontiers in Marine Science, 2021)
The characterization of the internal microenvironment of symbiotic marine invertebrates is essential for a better understanding of the symbiosis dynamics. Microalgal symbionts (of the family: Symbiodiniaceae) influence diel fluctuations of in host O 2 and pH conditions through their metabolic activities (i.e., photosynthesis and respiration). These variations may play an important role in driving oxygen budgets and energy demands of the holobiont and its responses to climate change. In situ measurements using microsensors were used to resolve the O 2 and pH diel fluctuations in the oral arms of non-calcifying cnidarian model species Cassiopea sp. (the “upside-down jellyfish”), which has an obligatory association with Symbiodiniaceae. Before sunrise, the internal O 2 and pH levels were substantially lower than those in ambient seawater conditions (minimum average levels: 61.92 ± 5.06 1SE μmol O 2 L –1 and 7.93 ± 0.02 1SE pH units, respectively), indicating that conditions within Cassiopea’s oral arms were acidified and hypoxic relative to the surrounding seawater. Measurements performed during the afternoon revealed hyperoxia (maximum average levels: 546.22 ± 16.45 1SE μmol O 2 L –1 ) and internal pH similar to ambient levels (8.61 ± 0.02 1SE pH units). The calculated gross photosynthetic rates of Cassiopea sp. were 0.04 ± 0.013 1SE nmol cm –2 s –1 in individuals collected at night and 0.08 ± 0.02 1SE nmol cm –2 s –1 in individuals collected during the afternoon.